The Rate of Phosphatase and Tensin (PTEN) Gene Expression Loss in Prostate Cancer and its Link to Tumor Upgrading - Gharib, Atoosa; Aziminejad, Atefeh; Pourmotahari, Fatemeh; Kazeminejad, Behrang; Soleimani, Mohammad (Urology Journal, 2023)
Purpose: Recent studies have provided reliable evidence for a relationship between loss of PTEN gene expression and prognosis in patients suffering from prostate cancer, although the results have been somewhat diverse in different populations. We aimed to assess PTEN gene expression loss by immunohistochemistry in prostate cancer and also its link to tumor upgrading in a group of affected patients undergoing radical prostatectomy. Materials and Methods: This cross-sectional study was performed on 58 tissue samples sourced from the patients with prostate cancer and undergoing radical prostatectomy. TRUS-guided needle biopsies of the cancer tissue samples with histological grade groups of I to IV (the Gleason scores of 6 to 8) were prepared as the study samples. 29 patients with Gleason score (6 to 8) whose tumors on needle biopsy upgraded to Gleason score 7, 8 or 9 at prostatectomy (cases) were compared with 29 patients with Gleason scores of 6, 7 or 8 on both biopsy and prostatectomy samples (controls). Immunohistochemistry (IHC) technique was employed to determine PTEN gene expression status. Results: Loss of PTEN gene expression was found in 62.1% of upgraded cases compared with 27.6% of controls, indicating a statistically significant difference, revealing a meaningful association between the loss of PTEN gene expression and tumor upgrading. Furthermore, we demonstrated that deletions of PTEN gene expression and increased Gleason score in control and upgraded case groups, did not reach statistical significance. Conclusion: A high rate of PTEN gene expression loss can be detected in prostate cancer tumor tissue, and this loss of gene expression is associated with tumor upgrading.